METODE PERHITUNGAN MASSA GAS CO2 YANG DISERAP FOTOBIOREAKTOR DENGAN PERSAMAAN GAS IDEAL - Arif Dwi Santoso (Jurnal Teknologi Lingkungan, 2010)
BPPT conducted the mass of CO2 gas calculation in the gas absorption experiments with phytoplankton cultivation in the photobioreaktor (FBR) batch and continous syatem using the ideal gas equation. This study stated that the method of calculation with the ideal gas equation is more simple and practical in providing data analysis compared with biomass methods. Some things to note in this method include good knowledge about the movement of the gas flow diagram of inputs and outputs FBR, an appropriate gas sampling, and accuracy of measuring instruments. The required data in the mass calculation of CO2 gas in a batch photobioreactor system was resultant CO2 concentration during measurement. Meanwhile in a continuous systems, the requireddata was CO2 concentration at the reactor input and output , the rate and duration of the injection gas.Keywods : massa gas CO2, dry weight, ideal gas formula